Vibrational Analysis of Free and Hydrogen Bonded Complexes of Nicotinamide and Picolinamide - Akalın, Elif; AKYÜZ, SEVİM (Elsevier, 2006)
Harmonic and anharmonic vibrations of free nicotinamide (NIA) and picolinamide (PIA) molecules together with their hydrogen bonded complexes H2O–NIA and H2O–PIA have been studied by means of density functional method. The calculation results of the vibrational spectra of free molecules have been investigated and are compared to the available experimental spectra. The vibrational wavenumbers of both molecules have also been calculated by polarizable continuum model (PCM) that represents the solvent as a polarizable continuum and places the solute in a cavity within the solvent (water is chosen as the solvent in this study). The results of PCM calculations and the H2O–NIA, H2O–PIA complexes, are used to investigate the H-bonding interactions of both molecules with the water molecule. The harmonic wavenumbers have been scaled by proper factors obtained by comparing the observed versus calculated wavenumbers and it is shown that anharmonic corrections on the vibrational spectra provided a better agreement between the observed and calculated wavenumbers compared to the results obtained by scaling factor method.
Keywords: Ab Initio Calculations; Nicotinamide; Picolinamide; IR Spectra; Raman Spectra; DFT